KONFLIK LAHAN DI DESA SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR (KASUS KONFLIK TENURIAL) - Patma Wati; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is motivated by ulayat land or customary land belonging to villagers of Senama Nenek village controlled by PTP.N V to become oil palm plantation. The problems that arise from this research are what factors are behind the occurrence of village land conflicts Senama grandmother and how to solve the land conflict. Informant research as much as 6 (six) people that is R as informant 1 as well as key informant or key informant, ARC, SM.N, FR, M and F. This research was conducted in Senama Nenek village Tapung Hulu sub district of Kampar regency, the reason the writer choose Senama Nenek village because in Senama Nenek village there is a conflict of struggle for ulayat land and until now there has been no settlement. Data analysis technique used by using triangulation technique that is writer analyze data starting from field observation, looking for initial data, process data and make conclusion. Based on the above approach, found there are factors behind the occurrence of land conflicts that is, differences in cultural background, differences of individual or group interests, changes in value in society, efforts to solve land conflicts in Senama Nenek village with the results of research that is the negotiation between the villagers of Senama Nenek and PTP.NV which resulted in the decision that PTP.NV should find a replacement land of 2,800 Ha, mediating by holding meetings between the Senama Nenek Community and the Company mediated by the DPD, Ombudsman, Komnas HAM and the Government Area. Conciliation is by accelerating the realization of the agreement, and Arbitration is by involving a third party to resolve land conflicts in Senama Nenek village.Keywords: Land Conflict, Conflict Resolution, Grandma's Grandmother's Village